Crop Productivity, Grain Quality, Water Use Efficiency, and Soil Enzyme Activity as Influenced by Silicon and Phosphorus Application in Aerobic Rice (Oryza sativa). Issue 16 (7th September 2020) - Jinger, Dinesh; Dhar, Shiva; Dass, Anchal; Sharma, V. K.; Shukla, Livleen; Parihar, Manoj; Rana, Kiran; Gupta, Gaurendra; Jatav, H. S.
ABSTRACT: The experiments were conducted to evaluate the effects of silicon (Si) and phosphorus (P) application on crop productivity, grain quality, water-use efficiency (WUE), and soil enzyme activity in aerobic rice (AR) at Indian Agricultural Research Institute, New Delhi, India. Four levels each of Si (0, 40, 80, and 120 kg Si ha –1 ) and P (0, 30, 60, and 90 kg P2 O5 ha –1 ) were tested in a factorial randomized block design (FRBD) replicated thrice. The growth, yield and quality of AR were enhanced with increasing Si and P application rates and a similar trend was observed for WUE and soil enzyme activity. The highest grain yield of AR was recorded with 120 kg Si and 90 kg P2 O5 ha –1 followed by 80 kg Si and 60 kg P2 O5 ha –1 and the lowest in control. The grain, straw yield and water productivity increased by 10–40%, 5–30%, and 10.2–39%, respectively in different treatments over control. Though, all studied parameters showed increment with increasing dose of Si and P; however 60 kg P2 O5 and 80 kg Si ha –1 were statistically superior to their other respective doses. In conclusion, supplementation of Si and P fertilizers substantially increased the AR productivity in Trans-Gangetic plains of India (Figure 1 ).